Da'wah and Religious Harmony, Harmony in the Nation and State - Irwandi, Irwandi; Saad, Duskiman; Rais, Zaim; Toni, Hariya; Nazirman, Nazirman; Jemkhairil, Jemkhairil (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Da'wah normatively has a positive impact on the people, because the da'wah conveyed is a manifestation of God's love and affection for mankind. In its implementation, the preaching delivered by religious figures often raises problems regarding harmony between religious communities and between religions. So it is hoped that da'wah can become a tool for developing the values of tolerance between religious communities and between religions, so that tolerance creates harmony in social life, and upholds the rights of each citizen. The approach used in this research is a qualitative method. This research shows that da'wah delivered properly and correctly in accordance with the demands of Islamic teachings can have a positive impact on life both personally, in the community, in society and in the state. This harmony is created if the values of tolerance and moderation can be developed by involving several elements including, elements of the government, elements of religious figures, systems or regulations that have been established as well as, public trust in the values of truth that are adhered to and the methods of preaching that are used. In creating harmony between religious communities and between religions, we return to the da'wah methods stated in the Al-Quran and the Sunnah of the Prophet Muhammad.